Product Approach-Based RAFT Strategy in Teaching Writing Personal Letters - Pratiwi, Yoesis Ika; Raja, Patuan; Flora, Flora (Universitas Islam Negeri Raden Intan Lampung, 2024)
This present study aimed to find out 1) whether there is improvement in students’ writing, and 2) the problems during the implementation of product approach-based RAFT strategy in teaching writing. The sample of the research was a group of fifth grade students at School of Victory, Bandar Lampung. This quantitative research had one-group pretest-posttest design. The instruments were writing test and observation checklist. The data were analyzed using SPSS 21.0. The result showed that the students’ ability in writing personal letter improved as some tests done helped verify that the improvement of students writing ability was significant. As one of the writing aspects, content improved the most. The problems indicated during the treatments belonged to some criteria namely teachers’ attitude, lack of students’ concentration, learners’ perspective, lack of vocabulary, and lack of practice and repetition. It was asserted that product approach-based RAFT strategy helped students to understand the target text through the four stages of the product approach. Moreover, RAFT led the students to plan and organize their writing ideas. However, some students seemed to have some problems during the treatment which mainly specified on their concentration, perspective, and vocabulary mastery. It was indicated that one or two students needed more practice and repetition in writing way more than the treatments in this study could provide